Towards the in vitro reconstitution of proteobacterial carboxysomes - How, Jian Ann (Nanyang Technological University, 2021)
Carboxysomes are proteinaceous bacterial microcompartments that are part of the prokaryotic CO2 concentrating mechanism (CCM). Key components are an outer protein shell, the CO2 fixing enzyme Ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) and carbonic anhydrase (CA). In conjunction with active accumulation of HCO3- by inorganic carbon (Ci) pumps, the carboxysomes increase the amount of CO2 within to saturate Rubisco’s active sites. This enables Rubisco to function at its maximum catalytic efficiency. However, the assembly of carboxysomes, particularly of the α-carboxysomes is only partially understood. Here we aimed to recapitulate the assembly of the α-carboxysome using purified components of Acidithiobacillus ferrooxidans and Halothiobacillus neapolitanus, providing an experimental platform to dissect the underlying mechanism. In this work, the intrinsically disordered CsoS2 Rubisco linker protein was shown to undergo homotypic liquid-liquid phase separation (LLPS) in a salt sensitive manner to form condensates. This biochemical property is likely the driver of α-carboxysome assembly in vivo. Rubisco and the hexameric shell protein CsoS1A were demonstrated to partition into condensates composed of CsoS2. Native gel shift assays were performed to investigate these protein-protein interactions. The condensation and binding properties of CsoS2 were then mapped to its different domains using CsoS2 fragments. The N-terminal domain was found to drive LLPS and partition Rubisco, while the C-terminal tail was an essential element in partitioning CsoS1A. CsoS2 also contains numerous conserved cysteine residues, hinting redox plays a possible role in influencing in its behaviour. We present data which suggest disulphide bond formation altered the properties of the condensate, implying that redox chemistry is involved in regulating the biogenesis of the carboxysome. These findings are contributions toward a mechanistic appreciation of carboxysomal biogenesis. This work will inform synthetic biology applications towards enhancing photosynthesis and permit engineering strategies towards sequestration of problematic biochemistry.